Author Correction: The unpolarized macronova associated with the gravitational wave event GW 170817. (November 2017) - Covino, S.; Wiersema, K.; Fan, Y.; Toma, K.; Higgins, A.; Melandri, A.; D'Avanzo, P.; Mundell, C.; Palazzi, E.; Tanvir, N.; Bernardini, M.; Branchesi, M.; et al.
In the version of this Letter originally published, in the third paragraph of the text Kyutoku et al. were not correctly cited and the sentence should have read: "As pointed out by Kyutoku at al.28, in the case of high optical depth to electron scattering ( 1) and assuming spectral lines do not significantly depolarize the global emission, the linear polarization observed from the equatorial plane could be as high as a few per cent." Also, in the Author contributions section, the final sentence should have read: "C.G.M. contributed to the writing of the paper."